The Effect Of Scanning Technique On Students Reading Comprehension In Narrative Text - Riris Nurkholidah Rambe (PG PAUD FIP UNIMED, 2017)
The objective of this research entitled “The Effect of Scanning Technique on Students’ Reading Comprehension in Narrative Text” was to find out the effect of scanning technique on students’ reading comprehension. To answer the problem, the writer uses the theories: Amruster, Lehr, and Osbon (2003:10), Brown (2011), Grellet (1992), Howrd (2006:1), Jhon.W.Creswell (2009:12), Kustario (1988:1), Nuttal (1982:34), Pang (2003:6), Sarwono (2013). This thesis has done deal with descriptive quantitative method. The writer uses the first year students as population and takes 60 students as samples. The instrument to get the data the writer uses pre-test and post-test. The collected data were analyzed by using T-test formula. The result of data analysis showed that the mean score was 74.4 and the standard deviation was 6.7. based on the data analysis above, the alternative hypothesis was accepted because the T-observed was higher than T- table (3.83>2.00). it means that Teaching Reading Using Scanning Technique was effective to improve students’ reading comprehension.